Mechanical and Acoustic Emission Characteristics of Sandstone through Triaxial Unloading Test after Cyclic Freezing-Thawing Treatment - Xiaohui Ni; Xiaomei Shen; Zhende Zhu (Advances in Civil Engineering)
The dynamic failure behaviour of tunneling rock in the cold region where freezing-thawing frequently occurs is unclear. This study aimed to test and understand the damage characteristics of tunneling sandstone samples in the cold region via triaxial unloading test and acoustic emission (AE) technique. The sandstone samples were first subject to different cycles of freezing-thawing. Their stress-strain curves, deformation modulus, and the AE characteristics were then measured under triaxial unloading conditions and through the AE test. The results showed that the freezing-thawing treatment with less than 60 freezing-thawing cycles caused rather less damage compared to the triaxial unloading condition. For the samples subject to more severe freezing-thawing treatment, more cracks were produced. These cracks were not closed under small confining pressure during the triaxial test, causing weaker mechanical properties of samples. We also found that the freezing-thawing treatment had a significant deterioration on the mechanical properties of the sandstone samples when the number of freezing-thawing cycles exceeded a certain threshold (between 60 and 80 in this study). As the AE characteristics matched well with the key stages of the measured axial stress-strain curves and the deformation modulus that varied with the decreasing confining pressure, the AE characteristics can be potentially used to quantify the released energy of rock cracking and identify the critical damage phases during the tunneling engineering process.